2019
DOI: 10.1002/1873-3468.13709
|View full text |Cite
|
Sign up to set email alerts
|

Rates and pathways of energy migration from the phycobilisome to the photosystem II and to the orange carotenoid protein in cyanobacteria

Abstract: Edited by Ulf-Ingo Fl€ uggeThe phycobilisome (PBS) is the cyanobacterial antenna complex which transfers absorbed light energy to the photosystem II (PSII), while the excess energy is nonphotochemically quenched by interaction of the PBS with the orange carotenoid protein (OCP). Here, the molecular model of the PBS-PSII-OCP supercomplex was utilized to assess the resonance energy transfer from PBS to PSII and, using the excitonic theory, the transfer from PBS to OCP. Our estimates show that the effective energ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 67 publications
0
10
0
Order By: Relevance
“…The shortcut connecting the FRL- PBSs to the FRL-PSII RCs is likely to involve an intermediate Chl in the antenna (CP43/47 paralogs) acting as a bridge. Indeed, structural data on canonical PBSs have shown that the pigments in the APC core are too far from those of the PSII RC to allow direct energy transfer between them 8 , 9 , 33 . To allow for faster trapping of bilin excitations, this bridging Chl in the antenna needs to be better connected to the RC than most other red-shifted Chls and, to avoid energetic barriers when receiving excitations from FRL-PBSs, it is likely to be red-shifted as well.…”
Section: Discussionmentioning
confidence: 99%
“…The shortcut connecting the FRL- PBSs to the FRL-PSII RCs is likely to involve an intermediate Chl in the antenna (CP43/47 paralogs) acting as a bridge. Indeed, structural data on canonical PBSs have shown that the pigments in the APC core are too far from those of the PSII RC to allow direct energy transfer between them 8 , 9 , 33 . To allow for faster trapping of bilin excitations, this bridging Chl in the antenna needs to be better connected to the RC than most other red-shifted Chls and, to avoid energetic barriers when receiving excitations from FRL-PBSs, it is likely to be red-shifted as well.…”
Section: Discussionmentioning
confidence: 99%
“…By reorganizing [1] we obtain: The k value is interpreted as an additional loss in the energy transfer efficiency with excitation using amber light compared to that with excitation using blue light and is equivalent to a change in the energy transfer efficiency from PBSs to PSII. The energy transfer efficiency is implicitly explained by Förster resonance energy transfer mechanism and determined by the distance between the PBS and PSII (Krasilnikov et al, 2020). A constant k level may therefore reflect a constant distance on average at which PBSs are detached from PSII.…”
Section: Discussionmentioning
confidence: 99%
“…If the energy transfer efficiency follows the Förster resonance energy transfer mechanism in which the efficiency is inversely proportional to the sixth power of the distance between the donor and acceptor pigment, an increase of distance by ∼10% is needed for the value of k to be 1.8. A slight shift of less than 0.5 nm in distance suffices to induce the energetic decoupling of PBSs from PSII as the shortest distance of the two pigments between the PBS and PSII is ∼4 nm (Chang et al, 2015; Krasilnikov et al, 2020). Such a mechanistic view is compatible with the previous finding that no mobile PBSs between PSII and PSI was observed in another extremophilic red alga C. caldarium using FRAP analysis (Kaňa et al, 2014), since PBS movement of less than one nanometer can result in strong energetic decoupling and is not detectable under light microscope.…”
Section: Discussionmentioning
confidence: 99%
“…The implemented in (Krasilnikov et al 2020) model of PBS docking to the PS II dimer on the surface of the thylakoid membrane was tested for the possibility of energy transfer via the PBLcm energy channel and for agreement between the calculated and experimental transfer times. The excitonic coupling model of the OCP and PBLcm interaction, previously well established (Krasilnikov et al 2020;Stadnichuk et al 2015), was then revised in accordance with the course of energy transfer from PBLcm to PS II, as well as the PBS to OCP cell ratio. In this way, we show that, within the framework of the model constructed, the times of energy transfer from the PBLcm to the PS II and from the PBLcm to the OCP are closely correlated.…”
Section: Introductionmentioning
confidence: 99%
“…2015;Krasilnikov et al 2020). Considering the thickness of the apoprotein layer over the near-surface chlorophylls of PS II and the gap created by this protrusion and the amorphous PBLcm loop exposed from the PBS core towards the thylakoid membrane, the distance of 42 Å most likely offered by the model(Krasilnikov et al 2020) was used here to provide an opportunity for energy transfer from PBS to PS II.…”
mentioning
confidence: 99%